Fiqh of Neuroscience: Neuron Transmission in Worship and Religious Dynamics of Covid-19 Survivors during the Period of Self-Isolation - Fatarib, Husnul; Hayati, Suci (Nizham Jurnal Studi Keislaman, 2024)
Neuroscience is a discourse that is always interesting to discuss with various perspectives, such as neuron studies with psychological, ecological, religious approaches and so on. The study of neurons integrated with fiqh is something new and fresh to be discussed globally. Neuroscience jurisprudence is a model of fiqh discovery using a sense, soul and mental approach as an inseparable part of the holy conscience engagement model, or also biased by the perspective of conscience satisfaction in carrying out worship. Nerve cells driven by transmitters such as adrenaline, acetylcholine, dopamine and others play an important role in stimulating neurons to integrate with each other in encouraging someone to do something. The presence of this paper by offering the formulation of neuroscience fiqh is an addition to the enthusiasm and passion for fiqh science connected to human nerve cell networks, giving rise to fiqh formulations that are very rich in aspects of taste and mentality that have so far been rarely empowered.